Recent advances and perspectives of postoperative neurological disorders in the elderly surgical patients. (3rd December 2021) - Liu, Biying; Huang, Dan; Guo, Yunlu; Sun, Xiaoqiong; Chen, Caiyang; Zhai, Xiaozhu; Jin, Xia; Zhu, Hui; Li, Peiying; Yu, Weifeng
Abstract: Postoperative neurological disorders, including postoperative delirium (POD), postoperative cognitive dysfunction (POCD), postoperative covert ischemic stroke, and hemorrhagic stroke, are challenging clinical problems in the emerging aged surgical population. These disorders can deteriorate functional outcomes and long‐term quality of life after surgery, resulting in a substantial social and financial burden to the family and society. Understanding predisposing and precipitating factors may promote individualized preventive treatment for each disorder, as several risk factors are modifiable. Besides prevention, timely identification and treatment of etiologies and symptoms can contribute to better recovery from postoperative neurological disorders and lower risk of long‐term cognitive impairment, disability, and even death. Herein, we summarize the diagnosis, risk factors, prevention, and treatment of these postoperative complications, with emphasis on recent advances and perspectives. Abstract : This review described general features and the latest evidence‐based knowledge of postoperative neurological disorders with emphasis on recent advances and perspectives. This review mapped the existing evidence regarding risk factors, prevention, and treatment for postoperative neurological disorders to help guide future research and clinical management.